The economics of the world trading system - Bagwell, Kyle (MIT Press, 2002)
World trade is governed by the rules of the World Trade Organization (WTO), the successor to the General Agreement on Tariffs and Trade (GATT). The WTO sets rules of conduct for the international trade of goods and services and for intellectual property rights, provides a forum for multinational negotiations to resolve trade problems, and has a formal mechanism for dispute settlement. It is the primary institution working, through rule-based bargaining, at freeing trade. In this book, Kyle Bagwell and Robert Staiger provide an economic analysis and justification for the purpose and design of the GATT/WTO. They summarize their own research, discuss the major features of the GATT agreement, and survey the literature on trade agreements. Their focus on the terms-of-trade externality is particularly original and ties the book together. Topics include the theory of trade agreements, the origin and design of the GATT and the WTO, the principles of reciprocity, the most favored nation principle, terms-of-trade theory, enforcement, preferential trade agreements, labor and environmental standards, competition policy, and agricultural export subsidies.